Pengaruh Strategi Pembelajaran Critical Incident terhadap Keterampilan Analisis Siswa - Sulastri, Sulastri; Safahi, Luthpi; Susilo, Susilo (Assimilation: Indonesian Journal of Biology Education, 2018)
The development of science and technology causes education to become a necessity for the younger generation. Based on the results of the survey, students analytical skills are still low, so an active learning strategy is needed that can improve students' analytical skills. Active learning strategies that can be used are Critical Incident strategies. This study aims to determine the effect of using Critical Incident learning strategies on students' analytical skills on the subject of environmental change. The research was carried out in class X MAN 9 Jakarta from March to June 2017. The research method used was quasi-experimental research design using posttest only control design. The population of this study were all students of class X MIA totaling 104 students. The data collection uses a multiple-choice test consisting of 24 items that are integrated with three types of indicators of analytical skills that are differentiating, organizing and attributing. The results showed that the average posttest value of the analytical skills of the experimental class was 64.88 while the control class was 62.49. Hypothesis testing through t-test at the significance level Î± = 5% obtained t count = 1.74 while t table = 1.67, because t count is greater than t table then H0 is rejected and H1 is accepted. Thus, it can be concluded that the use of Critical Incident learning strategies influences the analytical skills of class X MAN 9 Jakarta students.